Intellectuals and Japanese Buddhism in Brazil - Albuquerque, Eduardo Basto de (Japanese journal of religious studies, 2008)
This study concentrates on the discovery of Japanese Buddhism by Brazilian intellectuals as a group of spiritual practices and as a body of spiritual wisdom. The study has been realized through readings and meetings with Japanese Buddhist monks and/or Japanese immigrants. These intellectuals defend a religious experience based on a universal notion of representations of Japanese Buddhism, which provides them with a non-dualistic philosophical perspective and a unique psychological experience. Through innovative spiritual experiences these intellectuals have broken the tension created within the dispute between secularized science and the Catholic hegemony, both predominant in the intellectual panorama.